Antimicrobial Activity of Acacia tortilis (Talha of Tindouf) against Bacteria and Fungi Isolated from Various Water Sources in the Elbayadh Region (Algeria) - Snoussi, Moghtet; Najett, Menad; Hassen, Benyagoub El; Djahira, Hamed; Djamel, Ait Saada (Indian Journal of Pharmaceutical Education and Research)
Background: In El Bayadh province, water is an essential resource for survival, prompting residents to settle in areas next to water springs that provide drinking water and support livestock. Water contamination poses a significant threat to humanity, especially in the El Bayadh region. Biological contamination is a substantial risk to water sources. Our research focused on the utilization of medicinal plants to alleviate pollution. Phytochemicals have numerous medical applications and have antibacterial and antifungal characteristics. Materials and Methods: This study sought to assess the antimicrobial properties of Acacia gum sourced from Tindouf (Algeria) against microbes isolated from various water sources in El Bayadh (Algeria) via physical and chemical analyses (pH and temperature were measured using a Whitman PHA 260 pH meter) and microbiological analyses (the membrane filtration method was employed to quantify and compare microbial counts). To assess the biological impact of acacia gum, we formulated five concentrations of the substance (0%, 25%, 50%, 75%, and 100%). We integrated it with forty water samples (10 from the valley, 10 from the dam, 10 from taps, and 10 from mineral sources) and subsequently performed a series of physical, chemical, and microbiological tests. Results: The cytotoxicity assay of acacia gum exhibited no activity at any concentration tested for cytotoxic effects (active nauplii). Regarding the direct impact on aquatic microbes, we observed a marginal reduction in microbial colonies relative to the findings from the direct analysis and the assessment performed 24 hr post-application of the plant extracts to the valley water. Acacia gum exhibited a more pronounced biological effect on bacteria and molds. Their presence in the water is due to fecal pollution. Conclusion: Acacia gum exhibited a more pronounced biological effect on bacteria and molds. Enterococci are microorganisms with a notable capacity for environmental adaptation. They inhabit the intestines of around 75% of humans, and their presence in water results from fecal pollution.
Keywords: Water; Acacia gum; Antibiological effect; Physico-chemical and Microbiological analysis.